Implementasi Pendidikan Karakter Melalui Kegiatan Keagamaan di SD Islam Darush Sholihin Bagbogo Tanjunganom Nganjuk - Silfiya Nur Azizah; Muhammad Afthon Ulin Nuha (IAIN Ponorogo, 2023)
This study aims to analyze the implementation of character education through religious activities at SD Islam Darush Sholihin Bagbogo Tanjunganom Nganjuk. This is motivated by the phenomenon of moral decline in students so that the role of character education is very important, one of which is realized through religious activities. This research uses a qualitative approach with a descriptive type of research. Data collection techniques with observation, interviews, and documentation. The data analysis techniques used are data condensation, data testing and drawing conclusions. The results showed that (1) Forms of religious activities in improving character education at Darush Sholihin Islamic Elementary School include shaking hands when arriving at school, iftitah activities, reciting with the ummi method, congregational dhuha prayers, congregational dhuhur and ashar prayers, Friday prayers, memorization activities, kitabah, daughterhood / studies about women, hadrah art activities, and PHBI activities (2) Character formed in students through religious activities in elementary schools Darush Sholihin Islam includes religious character values, honesty, discipline, caring, independent, communicative, mutual help, curiosity, hard work, and responsibility (3) Obstacles in implementing character education through religious activities at Darush Sholihin Islamic Elementary School include internal factors (lack of preparation, some teachers do not condition activities well) and external factors (family environment, school environment, facilities and infrastructure).